Legal Consequences Of Default In Agreement Sale And Purchase Of Land Rights - Hardi, Prima Lestari; Daming, Saharuddin; Mustika, Desty Anggie (JURNAL MAHASISWA YUSTISI, 2023)
Law in its purpose to regulate daily life in society has been divided into two parts, namely Private Law, which regulates legal relations between one person and another, and Public Law, which regulates legal relations between legal entities. An engagement is one part of private law, which can be interpreted that in an engagement relationship this involves individual parties who bind themselves to each other which in the future will have legal consequences in the form of rights and obligations that have been mutually agreed upon in the agreement that has been agreed upon by the willing parties. If one of the willing parties does not fulfill his obligations in an agreement, then the party who does not fulfill his obligations is declared to have defaulted so that the other party in the agreement does not get the rights he should get from the fulfillment of that obligation. To know more clearly about the legal consequences of default in Indonesian binding law, the problems raised in this paper are: 1. How is the application of the legal consequences of default in Bogor District Court Decision Number 181/Pdt.G./2020/PN Bgr? 2. How is the legal protection of the rights of the injured party in default in Bogor District Court Decision Number 181/Pdt. G/2020/PN Bgr? The author uses a normative juridical method that uses sources of information.